2008
DOI: 10.1212/01.wnl.0000338460.89796.06
|View full text |Cite
|
Sign up to set email alerts
|

Is the common LRRK2 G2019S mutation related to dyskinesias in North African Parkinson disease?

Abstract: entered into the regression model are acknowledged. Thus, our findings need validation in an independent sample. Furthermore, we did not study whether the relationship of renal function and outcome differed between rtPA-treated and non-rtPA-treated patients.In conclusion, impaired renal function before thrombolysis is associated with increased odds for a poor outcome and with a trend to more SICH compared to stroke patients with normal renal function. ACKNOWLEDGMENTThe authors thank the patients and their fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…The p.Gly2019Ser mutation, although absent in more than 10,000 control individuals reported to date [Carmine Belin et al, 2006;Lesage et al, 2006;Ozelius et al, 2006;Papapetropoulos et al, 2006;Ross et al, 2006;Zabetian et al, 2006a], has also been identified in some asymptomatic individuals (16), of which one was 89 years old [Kay et al, 2005]. In addition, four clinically unaffected individuals of Algerian and Tunisian origin were found to be homozygous p.Gly2019Ser carriers (ages 41, 42, 45, and 70 years) [Ishihara et al, 2006;Lesage et al, 2008]. And although p.Arg1628Pro and p.Gly2385Arg variants are present in the control population with an overall frequency of 2.65% and 1.8%, respectively; they have been found to be significantly more prevalent in PD cases than in controls among individuals of Asian ancestries, suggesting that they act as risk factors for PD (Table 1).…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
“…The p.Gly2019Ser mutation, although absent in more than 10,000 control individuals reported to date [Carmine Belin et al, 2006;Lesage et al, 2006;Ozelius et al, 2006;Papapetropoulos et al, 2006;Ross et al, 2006;Zabetian et al, 2006a], has also been identified in some asymptomatic individuals (16), of which one was 89 years old [Kay et al, 2005]. In addition, four clinically unaffected individuals of Algerian and Tunisian origin were found to be homozygous p.Gly2019Ser carriers (ages 41, 42, 45, and 70 years) [Ishihara et al, 2006;Lesage et al, 2008]. And although p.Arg1628Pro and p.Gly2385Arg variants are present in the control population with an overall frequency of 2.65% and 1.8%, respectively; they have been found to be significantly more prevalent in PD cases than in controls among individuals of Asian ancestries, suggesting that they act as risk factors for PD (Table 1).…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
“…Frequencies ranged from the no cases to 35.7% in sporadic and 42% in familial North-African Arab patients (Brás et al 2005;Lesage et al 2005Lesage et al , 2006Lesage et al , 2008Clark et al 2006;Deng et al 2006;Gaig et al 2006;Goldwurm et al 2006;Infante et al 2006;Ozelius et al 2006;Marongiu et al 2006;Mata et al 2006Mata et al , 2009bCivitelli et al 2007;Cossu et al 2007;Ferreira et al 2007;González-Fernández et al 2007;Ishihara et al 2007;Orr-Urtreger et al 2007;Perez-Pastene et al 2007;Squillaro et al 2007;Hulihan et al 2008;Munhoz et al 2008;Pimentel et al 2008;Correia Guedes et al 2009;De Rosa et al 2009;Floris et al 2009;Gorostidi et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the frequency of LRRK2 G2019S in North African populations is 30–42% in familial PD [3,4,5,6] and 30–34% in apparently sporadic PD [6,7]. Recently the international LRRK2 consortium reported a worldwide frequency of 1% of LRRK2 G2019S in ‘sporadic’ PD and 4% in familial PD, with the highest frequency of LRRK2 G2019S being observed in ‘North African Arabs’ (39% of sporadic and 36% of familial PD), consistent with the earlier observations [1].…”
Section: Lrrk2 G2019s In the North African Populationmentioning
confidence: 99%
“…Emerging data, however, seem to suggest that patients with the LRRK2 G2019S mutation from North Africa have a more severe motor phenotype, and especially more dyskinesias and drug-induced dyskinesias [6,9]. In the study by Lesage et al [6], levodopa-associated dyskinesias were more evident in G2019S carriers than in non-carriers, even after correction for (longer) treatment duration. These observations, if validated, may have diagnostic and therapeutic implications for clinical practice, as well as providing insights into the biological mechanisms underlying drug-induced motor complications.…”
Section: Lrrk2 G2019s In the North African Populationmentioning
confidence: 99%